Nonsteroidal anti-inflammatory drug use is a risk factor for early Type II endoleak after endovascular abdominal aortic repair. (February 2020) - Matsubara, Yutaka; Inoue, Kentaro; Mori, Kazuki; Morita, Masato; Takebayashi, Satoshi; Kume, Masazumi
Objectives: Type II endoleak is a problem after endovascular abdominal aneurysm repair. Preoperative risk factors for Type II endoleak include anatomical factors in the lumbar artery and inferior mesenteric artery; however, preventable postoperative risk factors are unknown. Postimplantation syndrome is associated with lower incidence of Type II endoleak. Therefore, we focused on inflammation, and our aim was to investigate nonsteroidal anti-inflammatory drugs as a postoperative risk factor for Type II endoleak. Methods: This was a retrospective study of patients with aortic aneurysm who underwent endovascular aneurism repair at the Department of Cardiovascular Surgery, Beppu Medical Center, Oita, Japan, from January 2011 to August 2018. Clinical characteristics were retrieved from patients' medical records and included age, sex, body mass index, smoking history, comorbidities, treatment devices, medications, and perioperative information, including postimplantation syndrome. Postimplantation syndrome was defined as body temperature >38.5°C with 12, 000/dL white blood cells or >10.0 mg/dL C-reactive protein. The primary outcome was the presence or absence of Type II endoleak assessed on the first postoperative enhanced computed tomography scan. Risk factors for Type II endoleak were assessed. Results and conclusions: Of the eligible 84 patients, 20 (24%) had Type II endoleak identified in the first enhanced computed tomographic scans after endovascular aneurism repair. Nonsteroidal anti-inflammatory drug use (odds ratio (OR): 21.2; 95% confidence interval (95% CI): 1.5–308.4; P = 0.026), cerebrovascular disease (OR: 7.27; 95% CI: 1.06–49.99; P = 0.044), and body mass index <22 kg/m 2 (OR: 17.3; 95% CI: 2.1–141.8; P = 0.008) were independent risk factors for Type II endoleak after endovascular aneurism repair. Comparing the rate of Type II endoleak among patients who did not receive nonsteroidal anti-inflammatory drugs within 24 h after endovascular aneurism repair, patients who first used nonsteroidal anti-inflammatory drugs 12–24 h after endovascular aneurism repair, and those who received nonsteroidal anti-inflammatory drugs within 12 h after endovascular aneurism repair, we found a significant difference among the groups (4%, 18%, 45%, respectively; P = 0.001). Nonsteroidal anti-inflammatory drug use within 24 h after endovascular aneurism repair is a risk factor for Type II endoleak. We should know nonsteroidal anti-inflammatory drugs within 24 h after endovascular aneurism repair can be a risk of Type II endoleak.